Charting the path forward in Southeast Asia : Learning from the COVID-19 vaccination challenges in six ASEAN countries - Jolene Fu, Yin Ling; Muhammad Harith, Pukhari; Kristine, Alvarado-Dela Cruz; Amin, Soebandrio; Tan, Le Van; Watsamon, Jantarabenjakul; Anak Agung, Sagung Sawitri; Napaporn, Chantasrisawad; Sidney, Yee; Ruifen, Weng; Raghav, Sundar; Tan, Chee Wah; et al. (International Society of Global Health (ISoGH), 2024)
With a population exceeding 630 million (8% of the global population), the ten member states of the Association of Southeast Asian Nations (ASEAN) accounted for approximately 61 million (7.9%) of global COVID-19 cases and 808166 (11.6%) of deaths, with case fatality rate (CFR) of 1.3% by the end of 2023 [1]. The actual figures are certain to be at least several-fold higher, with estimates suggesting an excess mortality of 1.2 million in the first two years of the pandemic. Despite the World Health Organization’s (WHO) 4 May 2023 declaration that coronavirus disease 2019 (COVID-19) is no longer a public health emergency, it remains a global threat. The global response to the COVID-19 pandemic has highlighted the importance of collaborative networks within ASEAN, particularly in scientific information, technology and research exchange, resource mobilisation, and capacity building. While individual ASEAN country implemented responses with varying degrees of success, a unified and cohesive regional approach is crucial for early variant detection, efficient resource allocation, and evidence-based public health policies. Without collaborative efforts, the collective regional response weakens, jeopardising the region's preparedness for future health crises.